The Problem of Addressing in Explicit and Implicit Ways (Based on English and Uzbek Languages) - Ergashaliyeva Yulduz (Zien Journals, 2022)
This article identifies the use of addressing forms in formal and informal communication of comparable languages and linguistic analysis within different social groups. it is possible to identify communicative, pragmatic and linguocultural differences in the choice of language units. Moreover, it gives the brief information of using stylistic devices in addressing by explicit and implicit ways.
Keywords: Addressing; explicit; implicit